Effect of Bacillus Sp. Bacteria on The Growth of Saline Tilapia (Oreochromis niloticus) in The Biofloc System - Ikbal, Muhamad; Soadiq, Syawaluddin; ., Murni; Anwar, Asni; ., Akmaluddin; Malik, Abdul; ., Burhanuddin (Torani Journal of Fisheries and Marine Science, 2022)
One alternative to increase production is to maximize the use of biofloc system cultivation technology. However, the problems in biofloc cultivation are; the difficulty of cultivators to replace or alternatively use commercial bacteria to increase production. One of the efforts made is the use of bacillus sp. The aim of the study was to determine the optimal concentration of bacillus sp that could increase the growth of saline tilapia. This study used a completely randomized design (CRD) with four treatments, each repeated three times, so that there were 12 units. This study tested the concentration of Bacillus sp. 0.0028 ml/L, 0.0030 ml/L, 0.0032 ml/L, and 0.0034 ml/L. The results showed that the highest protein retention was 9.91%, fat retention was 2.05% and the body glycogen content of saline tilapia was 0.68%. This shows that the administration of Bacillus sp. in saline tilapia culture media has a real effect.